2022
DOI: 10.1007/s00004-022-00605-z
|View full text |Cite
|
Sign up to set email alerts
|

Parametric tools for Majolica Domes Modelling

Abstract: This paper presents some results of research aimed at defining a parametric tool for modelling complex decorative apparatuses of domes based on geometric rules definition and building techniques. MaTiDo, Majolica Tiles on Domes, is an adaptive tool that allows a user to place “fish scale” on revolution domes and oval or elliptical ones, on domes with ribs and domes without ribs. MaTiDo can be used to reproduce the look of the real domes and virtually reconstruct domes modified or destroyed. These ideal models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The creation of 3D objects was modeled according to parametric rules that can make them adaptive and thus reusable in multiple BIM projects. This has been increasingly used in VPL to generate 3D elements for HBIM (Capone and Lanzara 2022;Paris and Wahbeh 2016). The VPL approach to three-dimensional modeling has rapidly grown in recent years.…”
Section: The Researchmentioning
confidence: 99%
“…The creation of 3D objects was modeled according to parametric rules that can make them adaptive and thus reusable in multiple BIM projects. This has been increasingly used in VPL to generate 3D elements for HBIM (Capone and Lanzara 2022;Paris and Wahbeh 2016). The VPL approach to three-dimensional modeling has rapidly grown in recent years.…”
Section: The Researchmentioning
confidence: 99%
“…In particular, Lo Turco et al [10] apply the semantic decomposition method to model the decorative elements of architectural heritage windows, opening up the possibility of encoding geometric parameters in the VPL environment, which are useful for defining freeform or complex geometries within the BIM environment. On the other hand, Lanzara and Capone [11] define through VPL an algorithmic generative tool based on the definition of geometric rules and construction techniques for modeling the complex decorative apparatus of domes.…”
Section: State Of the Artmentioning
confidence: 99%
“…In particular, the earthquake of 30 July 1627 striking the Foggia area in the North and the event of 20 February 1743 occurred in the land of Otranto in the South (de Cadilhac, 2018). In both cases, the events profoundly marked the territory and the environment hosting these architectures and they triggered the need for reconstruction with novel solutions meeting both aesthetic and functional needs (Capone, 2022). The trinomial "needs, requirements and performances", cornerstone of the technical architecture and building engineering, finds an excellent synthesis then, since the different use of a known material to cover the domes responded to an economic need (the majolica tiles were certainly less expensive and therefore most used in the past), stood out for its distinctive artistic-architectural connotation of splendour and power and rationally resolved the waterproofing of the extrados after post-seismic structural consolidation works (de Cadilhac, 2018; Picone, 2020).…”
Section: Polychrome Majolica Domes Between History and Technique 21 H...mentioning
confidence: 99%
“…The scientific literature is focused on the topic, following two separate research lines that are found rarely convergent: on the one hand, the analysis and modelling of the "dome construction system" as structural and envelope component of religious monumental buildings (Zerlenga, 2021;Capone, 2022), on the other hand, the well-established research and characterization of the "ceramic material manufactured as majolica" (Coentro, 2012;de Viguerie, 2018]. This work aims to triggering some theoretical insights and operational procedures toward an integrated approach for reliable assessment and compatible intervention on such heritage, based on understanding the original constructive and performance requirements of an architectural unicum of resilient materials and techniques and defining general principles and remedies for the degradation factors affecting these elements nowadays.…”
Section: Introductionmentioning
confidence: 99%